New record of the non-indigenous crab Percnon gibbesi (H. Milne Edwards, 1853) from Palagruža archipelago (Adriatic Sea) - Dulčić, Jakov; Dragičević, Branko; Gašparević, Denis (2019)
Several individuals of non-indigenous grapsid crab Percnon gibbesi (H. Milne Edwards, 1853) have been observed and photographed in the area of Palagruža archipelago (Adriatic Sea, Croatia). This is additional confirmed record of this species in the Adriatic Sea. It suggests subsequent range expansion of this species and provides further evidence of its establishment in Adriatic waters.
Nekoliko jedinki nezavičajne vrste lakonogog raka, Percnon gibbesi (H. Milne Edwards, 1853) zabilježeno je i fotografirano na području palagruškog otočja.Ovdje se radi o novim potvrđenim nalazima za Jadransko more koji ukazuju na postupno širenje prema sjeveru te ujedno pružaju dokaz o uspostavi populacije ove vrste u Jadranu.
Bibliografija: 19 jed.
Summary ; Sažetak.
Keywords: Rakovi -- Percnon gibbesi -- Novi nalaz -- Invazivne vrste; Jadransko more -- Palagruža